Cytogenetic Effects of Honey Contaminated With Fumagillin (Dicyclohexylamine) on Male Mice Mus Musculus Balb/C In Vivo - Zuhdi, Soleen Sardar; AL-Asady, Asaad Abdulwahed B. (Science Journal of University of Zakho, 2013)
Cytogenetic effects of honey contaminated with fumagillin that collected from different sources in Duhok province was investigated in mouse bone-marrow cells using damaged cells%, (chromatids and chromosomal aberrations and mitotic index (M.I). A group of mice was orally administrated with honey that gave a positive result with qualitative chemical test. Fumagillin was administered to  another group of   mice by gavage, at doses of 25, 50, 75 mg/kg body weight (b.w) prepared with honey that give a negative result by   biochemical test  as artificially contaminant honey. All mice were treated for two different periods, 7 and 35 days at 24-hrs  intervals .The treated groups were compared with negative control and Cyclophosphamide (40 mg/kg bw) as a positive control. The biochemical test for all honey samples shows that 16.67% of honey samples were contaminated with fumagillin. The honey sample that give a positive result in the presence of fumagillin in biochemical test revealed its ability to increase the damage cell% and chromosomal aberrations in  bone marrow  cells after 7 and 35 days of treatment  .The ability of this sample equivalent to that of honey experimentally contaminated with fumagillin (25 mg/kg b.w).The result of the present study shows that the contaminated honey sample revealed its ability to reduce the M.I after 35 days of treatment in  bone marrow  cells as compared to negative controls.
Keywords: The